Online information adoption about public infrastructure projects in China. (10th August 2021) - Jiang, Hanchen; Zhang, Mengqing
Abstract: Public infrastructure projects are usually controversial and have huge impacts on the environment and society, thus attracting the attention from the broad public. Public understanding of engineering issues is important to the decision-making process of public infrastructure projects, but relevant empirical studies are still lacking in the literature. With a theoretical root of Elaboration Likelihood Model, this study empirically investigates the mechanism of online information adoption about public infrastructure projects based on 1877 answer data collected from Zhihu.com (an popular social Q&A site in China). Regression results show that: (1) information richness has an significantly positive effect on information adoption of an answer, (2) content features including professionalism, personal experience, entertainment, and anti-stigmatization have significantly positive effects on information adoption, (3) source credibility and source attractiveness have significantly positive effects on information adoption, and (4) source attractiveness negatively moderates the effect of information richness on information adoption. This research provides a better understanding of the mechanism of online information adoption and the formation of public opinion on controversial infrastructure projects.